2D Metals: 2D Metals by Repeated Size Reduction (Adv. Mater. 37/2016). Issue 37 (4th October 2016) - Liu, Hanwen; Tang, Hao; Fang, Minghao; Si, Wenjie; Zhang, Qinghua; Huang, Zhaohui; Gu, Lin; Pan, Wei; Yao, Jie; Nan, Cewen; Wu, Hui
Abstract : A general and convenient strategy for manufacturing metal nanosheets (e.g., Ag, Au, Fe, Cu, and Ni) on a large scale is developed by H. Wu and co‐workers, as described on page 8170. By repeated folding and calendering of stacked metal sheets, the thickness of each of the metal layers can be reduced to approaching 1 nm. The process is inspired by a traditional Chinese food called "thousand‐layer‐cake".